Maternal hepatitis B surface antigen carrier status and its impact on neonatal outcomes: a cohort study of 21 947 singleton newborns in China. (17th September 2017) - Tan, Jing; Huang, Shiyao; He, Guolin; Tang, Li; Ren, Yan; Zheng, Jinghuan; Liu, Xinghui; Sun, Xin
Abstract: Objective : To explore the impact of maternal hepatitis B surface antigen (HBsAg) carrier status on neonatal outcomes. Methods : A retrospective cohort study was conducted using data from medical records database of six hospitals in China. Information on maternal characteristics and selected neonatal outcomes was retrieved for all women who delivered singleton infants between 1 January 2009 and 31 December 2010. Results : A total of 21 947 singleton newborns and their mothers were included. The prevalence of maternal HBsAg positivity was 4.2% (95% confidence interval (CI) 3.9–4.5%). Compared with infants born to HBsAg-negative women, infants born to HBsAg-positive mothers were more than twice more likely to have a malformation before (adjusted odds ratio (aOR) 2.23, 95% CI 1.15–4.30) and at birth (aOR 2.66, 95% CI 1.38–5.14), but were less likely to be macrosomia (aOR 0.67, 95% CI 0.47–0.96). No statistically significant association was found between maternal HBsAg positivity and preterm birth (aOR 1.20, 95% CI 0.95–1.51), low birth weight (aOR 1.24, 95% CI 0.91–1.69), and Apgar scores at 1 min (aOR 0.88, 95% CI 0.49–1.57) and 5 min (aOR 1.84, 95% CI 0.89–3.81). Conclusion : Maternal HBsAg positivity may be associated with a higher risk of congenital malformation.